Enhancing the Mechanical Behaviour and Antibacterial Activity of Bioepoxy Using Hybrid Nanoparticles for Dental Applications - Mohammed, Mohammed Razzaq; Hadi, Ahmed Namah (International Journal of Biomaterials, 2022)
The appropriate capability of handling several forces exerted inside the mouth, and preventing the adhesion and proliferation of oral microorganisms are among the most vital factors for achieving effective alternative dental materials to the damaged native. Nevertheless, lack of mechanical and antimicrobial properties of dental resins hinders their use in most clinical applications in dentistry. In the present study, the main aim was to provide bioepoxy composite biomaterials that could meet the required mechanical and antibacterial properties for dental related fields. Herein, highly biocompatible epoxy and hybrid reinforcing materials were utilised to produce a composite material, which could have features resembling those of original dental parts. Various weight fractions of nanosilver/nano-alumina particles at 1, 2, and 3 wt% were incorporated into the bioepoxy for improving the mechanical and antibacterial characteristics of the biocompatible epoxy resin. Three-point bending and Izod impact tests were performed to evaluate the flexure and impact strengths of the obtained nanocomposites. The morphology of pristine bioepoxy and nanoparticle reinforced bioepoxy composites was characterized by scanning electron microscopy. The influence of these fillers on the bioepoxy resin antibacterial sensitivity was assessed using the agar diffusion technique. Nanofiller contents have been revealed to have a remarkable role to play in tuning the mechanical properties of the nanocomposites; the flexure strength and modulus were higher when the total ratio of hybrid reinforcement was 2 wt%. In contrast, the addition of higher percentage of hybrid nanoparticles could cause deterioration in the flexure characteristics of nanocomposites, yet they were better than those of pristine epoxy. Regarding the impact strength, the enhancement in this property was only observed for the composite containing 1 wt% of AgNps-Al2O3; the impact strength was dropped gradually beyond this ratio. The antibacterial effectiveness of the nanocomposites was demonstrated to positively depend on the increase in AgNps mass fraction. Among all evaluated unmodified and modified bioepoxy, the nanocomposite containing 2.5 wt% of AgNps had the higher antibacterial activity against Escherichia coli and Staphylococcus aureus. Based on the attainable outcomes, the prepared composites, particularly at moderate levels of Al2O3-AgNps, could provide biocomposites having the potential to be utilised in several biomedical fields, particularly in dental technology.